THE EFFECTS OF NOMINALIZATION IN NBCUNIVERSAL: A DISCOURSE ANALYSIS IN CORONATION 2023 - Sihura, Agnes Asnidar; Daniela, Lerissa (SIGEH ELT : Journal of Literature and Linguistics, 2024)
Media have been frequently emphasizing the information through headlines to as it usually conveys a catchy advertising-style headline and retrieves the gist of the story. Regardless of its contents, the headline becomes one of the most significant factors in attracting as much attention as possible from the readers. Therefore, choosing the appropriate headlines is crucial for the media to produce their intention properly to the readers. One of the ways is using nominalization. This research demonstrates the effects of nominalization on the headlines taken from NBCUniversal. The eight effects of nominalization by Machin and Mayr is utilized as the main theory of this study. Utilizing a qualitative method rooted in the Critical Discourse Analysis approach, the research data is the headlines sourced from the Coronation of King Charles III on NBCUniversal. From the total of eight effects, this study found six effects of nominalizations that appeared on the headlines of NBCUniversal media including, people and responsibilities are removed, the sense of time is removed, the action becomes a thing, the common usage as stable entities, the avoidance of the agent while accumulating a sense of action in the text, andthe compressed of the story details. The study also proved that understanding nominalization theory can help in generating captivating headlines to attract readers’ attention effectively.